A case study on microwave pyrolysis of waste tyres and cocoa pod husk; effect on quantity and quality of utilizable products. Issue 1 (February 2022) - Vaštyl, Michal; Jankovská, Zuzana; Cruz, Gerardo Juan Francisco; Matějová, Lenka
Abstract: Disposal of huge amounts of diverse wastes for reduced costs accompanied with gaining of energy and valuable chemicals is an eager topic in waste-to-energy and fuel business. Microwave pyrolysis is a thermochemical route providing such benefits. Waste scrap tyres (ST) and cocoa pod husk (CPH) as polymer and biomass representatives were pyrolyzed in microwave reactor at 440 W power for 30 min. Quantity and quality of pyrolysis products (gas, oil, and carbon black) were investigated. It was revealed, while set microwave pyrolysis conditions are sufficient for maximum decomposition of ST to pyrolysis products, it is necessary to optimize them for CPH. The gas produced by microwave pyrolysis of ST contains more H2 and CH4 than from conventional pyrolysis, thus, microwave pyrolysis is an effective tool for production of a fuel gas. The oil obtained by ST microwave pyrolysis is a complex mixture of mostly nonpolar aromatic compounds (toluene, benzene, limonene, styrene, o-xylene), while the oil obtained by CPH microwave pyrolysis contains mainly p-cresol, phenol and its derivatives. The ST-derived carbon black shows a well-established large-volume mesoporous-macroporous structure. The CPH-derived carbon black is a low-volume macroporous material with very well-developed microporosity. A higher gross calorific value of microwave ST-derived carbon black in comparison to conventionally prepared one is caused by its higher graphitization rate. Since the surface of ST-derived carbon black is more polar than CPH-derived one and with respect to chemical purity, it could be more suitable adsorbent for polar volatile organic compounds from gaseous emissions. It is necessary to develop a microporosity in ST-derived carbon black. Graphical Abstract: ga1 Highlights: Microwave pyrolysis as a tool for fuel gas production with increased H2 content. Tyres pyrolytic decomposition completed in 30 min at microwaves power of 440 W. Carbon black from CPH is turbostratic highly-microporous carbon. Carbon black from tyres is well-graphitized large volume meso-macroporous carbon. Cause of high GCV of microwave ST-derived carbon black is high rate of graphitization.